Creating a Culture-Based Language Learning Course for Developing Adult Learners’ 21st Century Skills - Luka, Ineta (Journal of Education Culture and Society, 2019)
Aim. The aim of the study is to research ways of developing adult learners’ 21st century skills in a culture-based language learning course applying innovative teaching/learning tools and methodologies considering adult learners’ specific needs and special educational treatment required to overcome learning barriers. Methods. Data collection methods include teachers’ accounts in the form of reflective essays on their pedagogical experience collected from 14 teachers. For data analysis and interpretation constant comparative method to elicit themes/categories and create construct mapping to make connections between ideas and themes has been used. Results and conclusion. An on-line learning course for adult learners, including blended-learning, must be based on classic adult learning principles considering the given socio-cultural context, learners’ backgrounds, needs, motivation, learning styles and strategies. The adult learners’ skills developed and cultural knowledge increased will help them in enriching their knowledge and competences, thus leading to higher upskilling and higher employability and quality, as well as becoming true lifelong learners. Research restrictions. The current paper deals with the analysis of the first stage of the research – teachers’ feedback and course creation. The second stage comprising observation and feedback obtained during the course piloting eliciting learners’ and teachers’ data will be analysed in a later article. Practical application. The research findings are useful in selecting suitable methodologies and approaches for language learning courses for adult learners, possibly for other courses as well. Originality/Cognitive value. The current research enables understanding adult learning context and specifics to secure special educational treatment required to overcome learning barriers and develop adult learners’ 21st century skills in a culture-based blended-learning course.